Evoking Interactivity: Film and Videogame Intermediality Since the 1980s. - MACK, JONATHAN (Adaptation, 2016)
Videogames have become a huge presence in the entertainment media landscape. From Pac Man (Midway, 1980) to Grand Theft Auto (Rockstar Games, 1997-2013), gaming has gained a level of mainstream engagement that has resulted in particular games and characters becoming reference points for popular culture in a way previously seen with iconic film and literature. How film has dealt with this growing popularity is particularly fascinating, revealing a great deal about how reproducing elements of the videogame form constitutes part of a strategy to remain relevant and compete for attention in an increasingly crowded media marketplace. Avoiding the common limitation of discussing films adapted from particular videogame properties, this paper explores films that deal explicitly with the game medium in their narratives. From Tron (Steven Lisberger, 1982) and The Lawnmower Man (Brett Leonard, 1992) to The Matrix (Andy and Larry Wachowski, 1999) and Source Code (Duncan Jones, 2011), I use the concept of interme-diality to demonstrate a clear increase in the engagement with and complexity of the interaction between games and films over time.